Kandungan Metabolit Sekunder Tempe Kacang Merah (Phaseolus vulgaris) - Lita Nur Hanifa; Sabaniah Indjar Gama; Laode Rijai (Proceeding of Mulawarman Pharmaceuticals Conferences, 2019)
Soybean is a bean that is basically used as raw material for making tempeh, but the need for soybeans is not balanced with the amount of production in Indonesia. Therefore it is necessary to study the secondary metabolites needed in red bean tempeh (Phaseolus vulgaris) for alternatives to soybeans as another raw material from non-soy beans produced from Indonesia. The purpose of this study was to determine the content of secondary metabolites present in red bean tempeh. Samples were obtained from the Sulawesi region. The analytical method used in this study are qualitative submitting flavonoids, alkaloids, terpenoids, tannins, and saponins. The results obtained from studies that have been carried out namely red bean tempeh are proven to have all the composition of secondary metabolites with the exception of saponins.